EVOLUTION OF MANAGEMENT SCIENCE - Norov, Asror (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Scientific formation and innovation management are two closely related areas of great importance for the development of modern society. In this article, we consider the stages and foundations of the scientific formation of innovation management, which are the main factors of the development of science and technology. The main stages and role of the scientific formation of innovation management in the modern world are considered in the article. The main stages of the evolution of management science under the influence of different schools and approaches are discussed.